Trade-in price and base warranty length: A heuristic algorithm for concurrent optimization. (September 2022) - Vafaeinejad, Kamyar; Sajadieh, Mohsen S.
Highlights: Joint implementation of the trade-in and base non-renewing warranty policies. Considering strategic customers reacting to price and warranty length. Proposing a heuristic algorithm based on the convexity of the models. Strategy level, innovation, quality, and production costs play the vital role. Abstract: The companies producing durable products consider various strategies to attract customers' attention and maximize their profit. The two inseparable policies utilized by these companies are free-replacement warranty and Trade-in. Both policies profoundly impact customers' buying behavior and producers' profit. In this article, we investigate a monopolist manufacturer producing durable products over a horizon of two periods. This manufacturer simultaneously implements trade-in and base warranty policies for the products and proffers them to strategic customers. The goal is to find the optimal products' prices, warranty length, and trade-in price, considering the influences of these parameters on the manufacturer's profit in each period. According to the warranty length and the length of each period, we developed two mathematical models. In these models, the uniform and exponential distributions are deemed as the failure distributions of the products, and a heuristic solution algorithm is then proposed based on the problems' convexity. The numerical study showed that the optimal warranty length and trade-in price are contingent on production costs, failure distributions, innovation, and strategy level. In addition, it is concluded that a higher trade-in price should be offered if the manufacturer chooses without warranty policy.